ALTERNATIVAS BIOLÓGICAS PARA EL CONTROL DE Spodoptera frugiperda (J. E. Smith) Y DE Helicoverpa zea (Boddie) EN CULTIVO DE MAÍZ DULCE (Zea mays var. saccharata), EN EL CANTÓN BABAHOYO - SANTANA ARAGONE DANILO XAVIER (2024)
The objective of this research was to propose products of biological origin as alternatives for the control of fall armyworms and earworms for the cultivation of sweet corn in the Febres Cordero parish, in the Babahoyo canton. Bandit F1 sweet corn was used as planting material. A randomized complete block design is used with seven treatments and three repetitions. The sample studied represents a set of 10 plants selected at random in each plot. The following variables are evaluated: Number of S. frugiperda larvae: at 15, 30, 45 and 60 days after sowing, percentage of damage (severity) in plants, number of H. zea larvae at 5 , 10, 15 and 20 days after the appearance of the female inflorescence, percentage of damage to ears, number of ears harvested per plot, plant height, yield in kg/ha-1 and treatment costs. Through the analysis of the results, it is evident that the use of biological alternatives is efficient for the control of Spodoptera frugiperda (J. E. Smith) and Helicoverpa zea (Boddie) in sweet corn (Zea mays var. saccharata) crops. In relation to the 15, 30, 45 and 60 days of evaluation of the presence of S. frugiperda larvae, the lowest averages were obtained in the treatment B. thuringiensis (2 g/L) + Vegetable oil (4 drops) with 4.33, 3.00, 2.67 and 1.00 larvae respectively. The lowest severity of damage by S. frugiperda was achieved with the treatment B. thuringiensis (2 g/L) + Vegetable oil (4 drops) with 2.97%. In relation to the 5, 10, 15 and 20 days of evaluation of the presence of H. zea larvae in the female inflorescence, the lowest averages were obtained in the treatment B. thuringiensis (2 g/L) + Vegetable oil ( 4 drops) with 4.33, 2.67, 1.33 and 0.67 larvae respectively. The lowest percentage of ears damaged by H. zea was achieved with the treatment B. thuringiensis (2 g/L) + Vegetable oil (4 drops) with 2.33% of ears damaged. In reference to plant height and number of ears per plot, the highest average was for the treatment B. thuringiensis (2 g/L) + Vegetable oil (4 drops) with 1.69 cm, and 233.33 ears per plot. In relation to the yield per hectare and economic analysis, the highest average was for the treatment B. thuringiensis (2 g/L) + Vegetable oil (4 drops) with 6266.67 kg/ha and with the highest net benefit with $460.20.